Reconstruction Method After Pancreaticoduodenectomy. Idea to Prevent Serious Complications - Osada, Shinji; Imai, Hisashi; Sasaki, Yoshiyuki; Tanaka, Yoshihiro; Nonaka, Kenichi; Yoshida, Kazuhiro (JOP. Journal of the Pancreas, 2012)
Pancreatic fistula after pancreaticoduodenectomy represents a critical trigger of potentially life-threatening complications and is also associated with markedly prolonged hospitalization. Many arguments have been proposed for the method to anastomosis the pancreatic stump with the gastrointestinal tract, such as invagination vs. duct-to-mucosa, Billroth I (Imanaga) vs. Billroth II (Whipple and/or Child) or pancreaticogastrostomy vs. pancreaticojejunostomy. Although the best method for dealing with the pancreatic stump after pancreaticoduodenectomy remains in question, recent reports described the invagination method to decrease the rate of pancreatic fistula significantly compared to the duct-to-mucosa anastomosis. In Billroth I reconstruction, more frequent anastomotic failure has been reported, and disadvantages of pancreaticogastrostomy have been identified, including an increased incidence of delayed gastric emptying and of pancreatic duct obstruction due to overgrowth by the gastric mucosa. We review recent several safety trials and methods of treating the pancreatic stump after pancreaticoduodenectomy, and demonstrate an operative procedure with its advantage of the novel reconstruction method due to our experiences.